1988
DOI: 10.1037/0021-9010.73.1.107
|View full text |Cite
|
Sign up to set email alerts
|

A new, more powerful approach to multitrait-multimethod analyses: Application of second-order confirmatory factor analysis.

Abstract: The advantages of applying confirmatory factor analysis (CFA) to multitrait-multimethod (MTMM) data are widely recognized. However, because CFA as traditionally applied to MTMM data incorporates single indicators of each scale (i.e., each trait/method combination), important weaknesses are the failure to: (1) correct appropriately for measurement error in scale scores; (2) separate error due to low internal consistency from uniqueness due to weak trait and/or method effects; (3) test whether items or subscales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
294
0
26

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(325 citation statements)
references
References 43 publications
5
294
0
26
Order By: Relevance
“…The chi-square value (χ 2 ) of 739.32 (df = 240, p < .001) was obtained, which indicates the goodness-of-fit. Furthermore, the χ 2 /df ratio was 3.081, which increases the acceptability of the model as it is within the acceptable range of 2 to 5 (Marsh & Hocevar, 1988). The other fit parameters of comparative fit index (CFI = .99) and normed fit index (NFI = .98) as well as the root mean square of approximation (RMSEA = .073) enhance the reliability of the model as they are below their acceptable levels (Byrne, 2010).…”
Section: Structural Model Evaluationmentioning
confidence: 98%
“…The chi-square value (χ 2 ) of 739.32 (df = 240, p < .001) was obtained, which indicates the goodness-of-fit. Furthermore, the χ 2 /df ratio was 3.081, which increases the acceptability of the model as it is within the acceptable range of 2 to 5 (Marsh & Hocevar, 1988). The other fit parameters of comparative fit index (CFI = .99) and normed fit index (NFI = .98) as well as the root mean square of approximation (RMSEA = .073) enhance the reliability of the model as they are below their acceptable levels (Byrne, 2010).…”
Section: Structural Model Evaluationmentioning
confidence: 98%
“…The new 32-item version of the DEU-MDDS was analyzed by exploratory factorial analysis again; it was shown that the DEU-MDDS had a two-componential factorial loading structure ( Table 3). [21][22][23][24] . The statistics on compliance of confirmatory factor analysis of the DEU-MDDS are given in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…This value describes excellent conformity when it has a value lower than three and it signs middle level conformity when it is lower than five (Marsh & Hocevar, 1988 …”
Section: Discussionmentioning
confidence: 99%
“…Özyeterlilik ve üstbiliş kavramlarının öğrencinin akademik başarısından, kaygı düzeyine birçok değişken üzerinde etkili olmasından dolayı eğitim alanında bu iki kavrama yönelik özellikle yurtdışında birçok araştırmaya rastlamak mümkündür (Bransford, Brown, & Cocking, 1999;Garcia & Pintrich, 1994;Klomegah, 2007;Multon, Brown, & Lent, 1991;White & Frederiksen, 1998  /sd oranının 3'ün altında olması yeterli uyum olarak kabul edilebilir (Şencan, 2005 Tablo 4 incelendiğinde t değerlerinin 2.576'nın üzerinde olduğu görülmektedir. Bu sebeple t-değerlerinin 0.01 düzeyinde tüm maddeler için anlamlı olduğu söylenebilir (Şimşek, 2007 Locke & Latham, 1990;White & Gunstone, 1989 Bu oranın 3'ten küçük olması mükemmel uyuma, 5'ten küçük olması ise orta düzeyde uyuma işaret etmektedir (Marsh & Hocevar, 1988). GFI ve AGFI değerleri ise sırası ile 0.92 ve 0.91 olarak belirlenmiştir.…”
Section: öZyeterlilik üStbiliş Ve öğRenme Süreçleri İle İlişkisiunclassified